The rising tide of color : race, state violence, and radical movements across the Pacific - Jung, Moon-Ho, 1969- (Emil and Kathleen Sick lecture-book series in western history and biography., 2014)
"The Rising Tide of Color challenges familiar narratives of race in American history that all too often present the U.S. state as a benevolent force in struggles against white supremacy, especially in the South. Featuring a wide range of scholars specializing in American history and ethnic studies, this powerful collection of essays highlights historical moments and movements on the Pacific Coast and across the Pacific to reveal a different story of race and politics. From labor and anticolonial activists around World War I and multiracial campaigns by anarchists and communists in the 1930s to the policing of race and sexuality after World War II and transpacific movements against the Vietnam War, The Rising Tide of Color brings to light histories of race, state violence, and radical movements that continue to shape our world in the twenty-first century. Moon-Ho Jung is the Walker Family Endowed Professor and associate professor of history at the University of Washington and the author of Coolies and Cane; "This brilliant volume is incisive, intellectually generative, and analytically rigorous. The Rising Tide of Color reframes our understanding of race and social movements by centering the Pacific Coast"--Diane Fujino, professor of Asian American Studies at University of California, Santa Barbara"--